La no renovación de contrato a los profesores de religión en las escuelas públicas por falta de idoneidad canónica : autonomía de las Iglesias y aconfesionalidad del Estado vs. derechos fundamentales del trabajador : comentario a las SSTC 38/2007 y 128/2007) - Brage Camazano, Joaquín (Teoría y Realidad Constitucional, 2007)
In this work, the author comments critically a recent case-law of the Constitutional Court about the cases in that the Administration doesn’t renew the yearly contract to a teacher of Catholic religion in public schools because the Bishop didn’t nominate him for that academic year because he failed to consider him a suitable teacher of religion, in part even on the basis of aspects related to his private life. In the Decision 38 of 2007, the Constitutional Court analyzes in abstract the compatibility with the Constitution of the Concordat which allows that «non renewall» of contract and it considers that this is in accordance with the Constitution but the Court lays down the demands that derive of the fundamental rights of the teacher and which should be kept in mind by the judges when enforcing this regulation to the concrete cases. In the Decision 128/2007, the Courth itself reviews a first concrete case of application of this doctrine. The Court gives great deference to the religious opinion of the Bishop when the «non renewal» is based on religious motivations in order to respect the collective freedom of religion.